THE EFFECT OF PARENTING STYLE ON NUTRITIONAL STATUS OF TODDLERS IN SURABAYA - Lisa Febrinda Nadhila; Astika Gita Ningrum; Mahendra Tri Arif Sampurna (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Nutrition is crucial for sustaining a golden phase over the first two years. Nutritional problems that develop early on will lead to more difficult future health problems. The most prevalent nutritional problems are found within the ages of 12 to 24 months. Purpose: to analyze the effect of parenting style on nutritional status of under two years babies. Methods: This study is an observational reasearch with cross-sectional approach. 685 toddlers and their parents made up the study's population, and a total of 75 were selected by accidental sampling. Anthropometric measures and questionnaires were used to gather the data. PSDQ (Parenting Style and Dimension Questionnaire) were used to identify parenting style. Results: Parenting styles for children's nutritional status were examined using the chi-square test, which revealed a value of 0.018. Conclusions: The study's findings suggest that parenting style and children's nutritional status are related.